Competitive psychophysiological fitness test system for blind judo Paralympics elite - Vinokurov, L. V.; Khalikov, R. R.; Baryaev, A. A.; Abramova, T. F. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test benefits the competitive psychophysiological fitness test system with analysis of the unconscious/ conscious psychophysiological fitness performance governed by the key nervous processes - in application to the national blind judo Paralympics elite.